(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The Pension Act depicts a drastic shift in the regulation of pension funds in Malawi. It becomes mandatory that every employer and employee contribute towards this fund till the end of employment. The labour concept differs from one country to another, one industry to another, time to time and between regions. Then, it depends on several problems on which the society has been confronted and moulded based on the sex, age group, economic status, soco-cultural background and also the educational level of employees in varied industries. Also, labour welfare in terms of the concept owns negative and positive sides such as, dealing with provision of the opportunities that allow workers along with their family to have a socially good life and also personally whereas, the negative side provides array of opportunities for labour problems and consequences. Moreover, it makes mandatory for every employer to keep up a life insurance policy on behalf of every employee. In order to provide people all sorts of social security and safeguard them from any kinds of exploitations, India had undertaken several welfare activities such as education for all, women empowerment, medical support for all, employment for an unskilled, semi-skilled, and skilled workforce, housing, and old age pensions. The financial and industrial policy of a state develops a roadmap for its comprehensive growth and development.